1999
DOI: 10.1099/0022-1317-80-4-1055
|View full text |Cite
|
Sign up to set email alerts
|

In vitro host range of Autographa californica nucleopolyhedrovirus recombinants lacking functional p35, iap1 or iap2.

Abstract: We have examined the host range in different insect cell lines of Autographa californica nucleopolyhedrovirus (AcMNPV) recombinants lacking p35, iap1 or iap2. These genes encode, or are predicted to encode, anti-apoptotic proteins. Abrogation of p35 reduced the ability of AcMNPV to replicate in permissive cell lines derived from Spodoptera frugiperda insects by inducing apoptosis. In semi-permissive cell lines, such as Lymantria dispar and Spodoptera littoralis cells, we observed cytopathic effects after infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 30 publications
0
29
1
2
Order By: Relevance
“…Op-iap3, like several other baculovirus iap genes, has been studied rather extensively outside of the context of infection by its native virus, but it had not been previously shown that any baculovirus iap gene is required to prevent apoptosis during a natural infection. Indeed, mutational analysis of the Ac-iap1 gene indicated that it is not required to prevent AcMNPVinduced apoptosis (21,39), although Ac-iap1 also lacks the ability to block apoptosis induced by other stimuli (14,27,31). Our findings demonstrate that Op-iap3 is important for preventing apoptosis during OpMNPV infection, indicating that other baculovirus iap genes that have the ability to block apoptosis outside of the context of virus infection are probably also required to prevent apoptosis during infection with their native virus.…”
Section: Discussionmentioning
confidence: 72%
“…Op-iap3, like several other baculovirus iap genes, has been studied rather extensively outside of the context of infection by its native virus, but it had not been previously shown that any baculovirus iap gene is required to prevent apoptosis during a natural infection. Indeed, mutational analysis of the Ac-iap1 gene indicated that it is not required to prevent AcMNPVinduced apoptosis (21,39), although Ac-iap1 also lacks the ability to block apoptosis induced by other stimuli (14,27,31). Our findings demonstrate that Op-iap3 is important for preventing apoptosis during OpMNPV infection, indicating that other baculovirus iap genes that have the ability to block apoptosis outside of the context of virus infection are probably also required to prevent apoptosis during infection with their native virus.…”
Section: Discussionmentioning
confidence: 72%
“…Since viruses should retain only genes that they need, it is interesting to speculate on the possible roles of these iap genes (9). In this paper, we found that iap2 of both HzNV-1 (8) and AcMNPV (3,15) can effectively suppress apoptosis induced by hhi1.…”
Section: Discussionmentioning
confidence: 85%
“…One possibility is that the genes have some functions irrelative to apoptosis. When infected with baculoviruses, many insect cells, such as AcMNPV-infected Ld652Y cells [32] or SpltNPV-infected SpLi-221 cells, show evident cytopathic effects including cell rounding and clumping in contrast to normal cells. Another study showed that deletion of Ac-iap1 resulted in a competitive advantage for AcMNPV replication in a Trichoplusia ni cell line, but not in a S. frugiperda cell line [33].…”
Section: Functional Assay Of Splt-iap4mentioning
confidence: 97%